Current clinical and epidemiological portrait of a patient with acute myocardial infarction (by the data of the regional vascular center) - E. Yu. Kovalchuk; V. V. Soroka (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Epidemiological and clinical presentation of acute myocardial infarction based upon the data collected in Regional Vascular Centre of Saint-Petersburg Scientific Research Institute of Emergency Care n. a. I. I. Dzhanelidze in 2009-2012 years. In the article, 4697 cases have been analyzed. Specific features of epidemiology and clinical presentation of acute myocardial infarction at the present stage have been considered.